The Role of Electronic-Based System in Minimizing Medication Error - Saho, Musa (Lentera Perawat, 2025)
Medication errors pose a critical challenge in healthcare systems, often resulting in preventable harm and compromised patient safety. These errors can occur at various stages of medication management, from prescribing to administration. The adoption of electronic-based systems, including Computerized Physician Order Entry (CPOE), Barcode Medication Administration (BCMA), and Automated Dispensing Cabinets (ADCs), has emerged as a transformative strategy to mitigate these risks. This article discusses the roles and benefits of these systems in reducing medication errors by enhancing process accuracy, enabling real-time verification, and supporting clinical decision-making. Although implementation challenges such as cost, staff resistance, and alert fatigue persist, the integration of electronic systems is essential for fostering a safer and more efficient medication delivery environment. Further advancements in artificial intelligence and system interoperability are expected to strengthen these technological interventions in the future.